Aesthetic considerations in localization decisions of city entrances - Uppala, Ella (2017)
Th is thesis is about the aesthetic qualities of highways that function as approach roads to cities, regions, and the diff erent municipalities of these regions. A ques-tion that is posed is about the relevance of aesthetic considerations in the locali-zation decisions of elements that signal approaching and entering areas along the highway: How can the need for cues of entrance be localized along city approach-es, based on aesthetic criteria formulated from the road user’s perspective? Th e question was deemed important for two reasons. Approach roads are a signif-icant part of many commuter’s daily landscape, and their aesthetic qualities have an eff ect on the commuters’ psychological processes, traffi c behavior and quality of life. As such, aesthetic considerations on approach roads are a part of the dis-cussion about the quality of people’s living environments in general. Th e second reason is specifi c to city approaches and –entrances as expressions of identity of a place and other meanings that change the road user’s impression of the places they are approaching, reaching and passing by. During the project it was found that the words “city entrance” and “city gate” have very strong connotations and associa-tions, especially on a regional level where each municipality and district vie for the honor of being called the entrance to the region. To better understand the multiple functions and values that elements in the road environment that signal approach and entering can have, a new, less loaded concept of “cues of entrance” was created. In order to understand what the role of aesthetics in the road environment and especially along approach roads is, a literature study was conducted. Th e literature study yielded a great amount of information about how the road user experiences the aesthetic aspects of their environment, and how they infl uence their further experience of the road and the places around it. Th e fi ndings of the literature study were then formulated into goals for the aesthetic components of the road environ-ment. Th ese goals can also serve as criteria for evaluating the suitability of a certain location for new cues of entrance. Th e practical inspiration for pursuing the subject was to create an analysis of the European highway E4/E20 in its role as the Southern Approach to Greater Stock-holm Region. Th e highway has been analyzed from the municipality of Botkyrka to the southern districts of Stockholm city, and evaluated from an aesthetic point of view. Th e aesthetic qualities of the road environment along the highway that contributed to a sense of approaching to or arriving in diff erent places were paid special attention to. Evaluating the analysis of the approach road E4/E20 according to the goals for the aesthetic components of the road environment resulted in recommendations for improving the road environment along the highway, in some cases by adding new cues of entrance in specifi c locations.